2021
DOI: 10.1039/d1nr01155c
|View full text |Cite
|
Sign up to set email alerts
|

In situ injection of dual-delivery PEG based MMP-2 sensitive hydrogels for enhanced tumor penetration and chemo-immune combination therapy

Abstract: Improving the deep penetration of nanoparticles and realizing the combination of chemotherapy and immunotherapy have become a promising strategy for cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…These results confirmed that the NB can enhance the therapeutic effect of CDT by the cellular redox homeostasis interference because of the NB with good biocompatibility when the concentration is lesser than 500 μg ml −1 (Supplementary Figure S6). Finally, the antitumor effect of NB/CuS@PCM NPs is also verified by PI staining (Yan et al, 2021). And the result was consistent with the MTT assay (Figure 3D, PI staining).…”
Section: Resultssupporting
confidence: 84%
“…These results confirmed that the NB can enhance the therapeutic effect of CDT by the cellular redox homeostasis interference because of the NB with good biocompatibility when the concentration is lesser than 500 μg ml −1 (Supplementary Figure S6). Finally, the antitumor effect of NB/CuS@PCM NPs is also verified by PI staining (Yan et al, 2021). And the result was consistent with the MTT assay (Figure 3D, PI staining).…”
Section: Resultssupporting
confidence: 84%
“…The Michael addition reaction is also utilized in drug delivery and the releasing of on-demand materials [ 106 ]. According to Guo et al, Diacrylate modified 8-arm PEG was crosslinked with MMP-sensitive peptide (CGPQG↓IWGQC) via the Michael addition reaction [ 107 ].…”
Section: Synthesis Of Mmp-cleavable Peptides-based Hydrogelsmentioning
confidence: 99%
“…Like “Domino-effect”, the chemotherapy combined with immunotherapy could amplify the efficacy of anti-tumor treatment. Studies have demonstrated that many advanced nanoparticles are competent to break through barriers in combinatorial chemo-immune treatment ( Wei X. et al, 2019 ; He et al, 2021 ; Yan et al, 2021 ). Notably, the latest study reveals the phenomenon that some nanomaterials possess the inherent biological effect on immunotherapy.…”
Section: Nanomaterials Therapeutics Overcome Drug Resistancementioning
confidence: 99%